HUMAN RESOURCE MANAGEMENT IN CRISIS COMMUNICATION WITHIN THE HEALTHCARE SECTOR: A CASE STUDY OF HOSPITALS IN GHANA - Adjei, Monica (Komitmen: Jurnal Ilmiah Manajemen, 2024)
This study investigates the role of human resource management (HRM) in crisis communication within the healthcare sector, focusing on hospitals in Ghana. Effective crisis communication is crucial in healthcare settings, especially during emergencies such as pandemics, epidemics, and other public health crises. This research explores the HRM strategies employed by hospitals to manage crisis communication and examines their impact on staff performance, patient outcomes, and overall crisis management effectiveness. Utilizing a mixed-method approach, the study combines qualitative interviews with healthcare administrators and HR managers with quantitative surveys of healthcare staff across several hospitals in Ghana. The findings reveal that robust HRM strategies, including targeted training, clear communication protocols, and employee support systems, are vital in enhancing crisis communication efforts. However, challenges such as inadequate training, resource constraints, and cultural barriers can undermine these efforts. The study provides insights into how HRM practices can be optimized to improve crisis communication and suggests practical recommendations for healthcare institutions and policymakers to strengthen their crisis preparedness and response.